Factors Associated With Attitude Toward Premarital Sexual Activities Among School-Going Adolescents in Kelantan, Malaysia. (March 2015) - Rahman, Azriani Abdul; Rahman, Razlina Abdul; Ismail, Shaiful Bahari; Ibrahim, Mohd Ismail; Ali, Siti Hawa; Salleh, Halim; Wan Muda, Wan Abdul Manan
The objective of this cross-sectional study was to determine the factors associated with the attitudes toward premarital sexual activities among school-going adolescents in Kelantan, Malaysia. It was conducted among 1032 secondary school students using a self-administered validated questionnaire. Multiple logistic regression revealed that the risk factors for having permissive attitudes toward practice of premarital sexual activities were male students (odds ratio [OR] = 1.83; 95% confidence interval [CI] = 1.34-2.48), being less religious (OR = 2.02; 95% CI = 1.49-2.73), and younger age group of students (13 to 14 years old; OR = 1.42; 95% CI = 1.05-1.92). Having good knowledge on sexual and reproductive health was a protective factor against permissive sexual attitude (OR = 0.27; 95% CI = 0.20-0.36). In conclusion, male and young adolescents were at risk of having permissive attitudes toward sexual behaviors, but good knowledge on sexual and reproductive health and being more religious may protect them from it.